Shared Pathogenetic Features Between Common Variable Immunodeficiency and Sjögren’s Syndrome: Clues for a Personalized Medicine - Quartuccio, Luca; De Marchi, Ginevra; Longhino, Simone; Manfrè, Valeria; Rizzo, Maria Teresa; Gandolfo, Saviana; Tommasini, Alberto; De Vita, Salvatore; Fox, Robert (Frontiers in Immunology, 2021)
Common variable immunodeficiency disorders (CVID) are a group of rare diseases of the immune system and the most common symptomatic primary antibody deficiency in adults. The “variable” aspect of CVID refers to the approximately half of the patients who develop non-infective complications, mainly autoimmune features, in particular organ specific autoimmune diseases including thyroiditis, and cytopenias. Among these associated conditions, the incidence of lymphoma, including mucosal associated lymphoid tissue (MALT) type, is increased. Although these associated autoimmune disorders in CVID are generally attributed to Systemic Lupus Erythematosus (SLE), we propose that Sjogren’s syndrome (SS) is perhaps a better candidate for the associated disease. SS is an autoimmune disorder characterized by the lymphocytic infiltrates of lacrimal and salivary glands, leading to dryness of the eyes and mouth. Thus, it is a lymphocyte aggressive disorder, in contrast to SLE where pathology is generally attributed to auto-antibody and complement activation. Although systemic lupus erythematosus (SLE) shares these features with SS, a much higher frequency of MALT lymphoma distinguishes SS from SLE. Also, the higher frequency of germ line encoded paraproteins such as the monoclonal rheumatoid factor found in SS patients would be more consistent with the failure of B-cell VDJ switching found in CVID; and in contrast to the hypermutation that characterizes SLE autoantibodies. Thus, we suggest that SS may fit as a better “autoimmune” association with CVID. Examining the common underlying biologic mechanisms that promote lymphoid infiltration by dysregulated lymphocytes and lymphoma in CVID may provide new avenues for treatment in both the diseases. Since the diagnosis of SLE or rheumatoid arthritis is usually based on specific autoantibodies, the associated autoimmune features of CVID patients may not be recognized in the absence of autoantibodies.